Death by ‘ice’: fatal methamphetamine intoxication of a body packer case detected by postmortem computed tomography (PMCT) and validated by autopsy - Abdul Rashid, Saiful Nizam; Abdul Rahim, Amir Saad; Thali, Michael J.; Flach, Patricia Mildred (Springer, 2013)
Fatal acute methamphetamine (MA) poisoning in cases of internal drug trafficking is rarely described in the literature. This case study reports an MA 'body packer' who died from fatal methamphetamine intoxication due to leaking drug packages in the alimentary tract. The deceased was examined by postmortem computed tomography (PMCT), and the results were correlated to subsequent autopsy and toxicological findings. The deceased was arrested by the police when he was found disoriented in the city of Kuala Lumpur. He was transferred to the emergency department on suspicion of drug abuse. The initial drug screening was reactive for amphetamines. Shortly after admission to the hospital, he died despite rigorous resuscitation attempts. The postmortem plain chest and abdominal radiographs revealed multiple suspicious opacities in the gastrointestinal tract attributable to body packages. An unenhanced whole body PMCT revealed twenty-five drug packages, twenty-four in the stomach and one in the transverse colon. At least two were disintegrating, and therefore leaking. The autopsy findings were consistent with the PMCT results. Toxicology confirmed the diagnosis of fatal methamphetamine intoxication.